Seismic microzonation and geotechnical characteristics of Manna City, South Bengkulu - Anjelah, Aza Geby; Mase, Lindung Zalbuin; Amri, Khairul; Misliniyati, Rena; Hardiansyah, Hardiansyah (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
As one of the disaster-prone areas in Manna, this city is prone to disasters. This study aims to evaluate the potential risk of earthquakes in Manna through a seismic microzonation approach. Using amplification factor and dominant frequency data, this study produced a microzonation map showing areas with a higher risk of earthquake damage. The methods applied in this study include the Horizontal-to-Vertical Spectral Ratio (HVSR) and Multichannel Analysis of Surface Waves (MASW), which enable analysis of soil properties and their influence on earthquake vibration amplification. The study results reveal that areas with soft soil and high amplification, such as Pasar Manna and Pino Raya, are at higher risk of significant damage during an earthquake. Based on these findings, we recommend mitigation measures such as spatial planning that considers seismic risk, the implementation of earthquake-resistant construction, and enhancing community preparedness. By integrating these microzonation results into development policies and disaster mitigation strategies, it is hoped that the city of Manna can reduce the potential damage caused by earthquakes.